A new energy consumption technique for mobile ad hoc networks - S. Alani; Zahriladha Zakaria; Herwansyah Lago (International Journal of Electrical and Computer Engineering (IJECE), 2019)
A dynamic temporary network is created through wireless mobile nodes without the need for considerable infrastructure as well as a central manager. In a mobile ad hoc network, routing protocols allow a mobile for transmission and receiving packets. In the last decade, many variants have come up for the AODV. A minimum number of hop counts are chosen for enhancing routing protocols to include additional factors that can have an impact on path selections. As the distance between each node grows, the transmission power also rises accordingly. Hence, this impacts the network’s entire performance and the most important feature is the quality of service. Most of the traditional routing protocols include energy consumption levels of the nodes and various parameters, like residual battery power, consumption of energy per packet and energy needed per transmission. A new technique is proposed in this paper to enhance the routing efficiency by making use of lion optimization algorithm after identifying all possible paths in the network. This technique not only enhances the energy efficiency of each node but also the performance metrics.